Innovation engine : driving execution for breakthrough results - Desai, Jatin (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
How to implement an innovation engine in any organization Innovation is often sought and is in high demand today. At the same time it is often misunderstood and lacks committed sponsorship. Today, most teams at the top need an innovation capability in a manner that works in tandem with their performance/operations management. Packed with actionable ideas, references, links, and resources, Innovation Engine meets that need. Reveals how to develop strategy, road maps, and processes for innovation executionProvides high level implementation guidance on executing in.
3. Identify Innovation Leaders and Best Talent4. Communicate, Communicate, Communicate; 5. Build Awareness-Educate Everyone; 6. Protect the Momentum; Conclusion; Note; Part III Playing the Game; Chapter 6 Structuring for Innovation; Components of Organizational Structure; Types of Organizational Structures; Traditional Structures; Matrix Structures; Program-Based Structures; Planning Your Innovation Structure; Four Major Types of Innovation Structures; Traditional Two-Tier Structure; Center of Excellence; Strategic Horizons Group; Intrapreneuring and Venturing Group.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Technological innovations -- Management; Diffusion of innovations -- Management; New products; Strategic planning; Diffusion of innovations -- Management; New products; Strategic planning; Technological innovations -- Management; BUSINESS & ECONOMICS -- Structural Adjustment; Electronic books; Electronic books